2021
DOI: 10.1177/02692163211006313
|View full text |Cite
|
Sign up to set email alerts
|

The experience of delirium in palliative care settings for patients, family, clinicians and volunteers: A qualitative systematic review and thematic synthesis

Abstract: Background: Delirium is common in palliative care settings and is distressing for patients, their families and clinicians. To develop effective interventions, we need first to understand current delirium care in this setting. Aim: To understand patient, family, clinicians’ and volunteers’ experience of delirium and its care in palliative care contexts. Design: Qualitative systematic review and thematic synthesis (PROSPERO 2018 CRD42018102417). Data sources: The following databases were searched: CINAHL, Cochra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 57 publications
0
27
0
Order By: Relevance
“…A recent international qualitative systematic review identified that practical and emotional support were needed to enable staff to assess, prevent and manage delirium. 15 A recent survey of palliative care doctors (n=335) in the UK found that 38% never used delirium guidelines and that only 13% of palliative care teams used a tool (rather than clinical judgement) to assess for delirium at first inpatient assessment, with even fewer (9%) using a tool on an ongoing basis. 16 Our survey of UK specialist palliative care units (n=220, mostly nurses) 17 found that only 10% ever used a delirium screening tool, with only 5% following NICE guidelines by screening on admission, and only 6% screening daily thereafter.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 2 more Smart Citations
“…A recent international qualitative systematic review identified that practical and emotional support were needed to enable staff to assess, prevent and manage delirium. 15 A recent survey of palliative care doctors (n=335) in the UK found that 38% never used delirium guidelines and that only 13% of palliative care teams used a tool (rather than clinical judgement) to assess for delirium at first inpatient assessment, with even fewer (9%) using a tool on an ongoing basis. 16 Our survey of UK specialist palliative care units (n=220, mostly nurses) 17 found that only 10% ever used a delirium screening tool, with only 5% following NICE guidelines by screening on admission, and only 6% screening daily thereafter.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…A recent international qualitative systematic review identified that practical and emotional support were needed to enable staff to assess, prevent and manage delirium. 15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,11 Clinicians as well often lack requisite knowledge and environmental resources to reduce patients' risk of delirium. 12,13 Cognisant of both the potential for and barriers to preventing delirium, in 2017-18 we conducted a phase II cluster randomised controlled trial of a multicomponent non-pharmacological delirium prevention intervention for patients with advanced cancer in four Australian palliative care units ('the PRESERVE pilot study'). 14,15 Recruitment and implementation were at the site level, with 65 patients across the four sites enrolled for quantitative data collection.…”
Section: Introductionmentioning
confidence: 99%
“…Delirium is an acute neurocognitive condition that adversely affects many people with life-threatening illness, as well as those who care for them. [1][2][3][4] Antipsychotics are widely used in palliative care for delirium. 5 Yet, in 2017, a large Australian multi-site, double-blind randomised controlled trial of risperidone or haloperidol or placebo for patients with disturbed perception, behaviour and/or communication during delirium in 11 palliative care units (the 'Agar et al 6 trial') reported significantly lower symptom scores, fewer extrapyramidal effects, lower use of crisis midazolam and better survival in participants receiving placebo.…”
Section: Introductionmentioning
confidence: 99%